Assessing Singapore's Role and Impact in SIDS Framework Case Study: Implementation The SAMOA Pathway - Anaaisyah, Risqi; Radhana, Javiar Duvadilan; Al Anwary, Muhammad Hanan Amin; Hidayatullah, M. Bintang; Aryokusumo, Brilliando Lintang (Department of International Relations Universitas Pertamina, 2023)
This research will evaluate Singapore's strategic role in supporting the implementation of the SAMOA Pathway framework for Small Island Developing States (SIDS), with a focus on the renewable energy agenda through the